Cancer and the Politics of Care Inequalities and interventions in global perspective - Bennett, Linda Rae; Manderson, Lenore; Spagnoletti, Belinda (Embodying Inequalities: Perspectives from Medical Anthropology, 2023)
This timely volume responds to the epic impacts of cancer as a global phenomenon. Through the fine-grained lens of ethnography, the contributors present new thinking on how social, economic, race, gender and other structural inequalities intersect, compound and complicate health inequalities. Cancer experiences and impacts are explored across eleven countries: Argentina, Brazil, Denmark, France, Greece, India, Indonesia, Italy, Senegal, the United Kingdom and the United States. The volume engages with specific cancers from the point of primary prevention, to screening, diagnosis, treatment (or its absence), and end-of-life care. Cancer and the Politics of Care traverses new theoretical terrain through explicitly critiquing cancer interventions, their limitations and success, the politics that drive them, and their embeddedness in local cultures and value systems. It extends prior work on cancer, by incorporating the perspectives of patients and their families, 'at risk' groups and communities, health professionals, cancer advocates and educators, and patient navigators. The volume advances cross-cultural understandings of care, resisting simple dichotomies between caregiving and receiving, and reveals the fraught ethics of care that must be negotiated in resource-poor settings and stratified health systems. Its diversity and innovation ensures its wide utility among those working in and studying medical anthropology, social anthropology and other fields at the intersections of social science, medicine and health equity.